High-Grade Transformation ("Dedifferentiation")—Malignant Progression of Salivary Gland Neoplasms, Including Carcinoma ex Pleomorphic Adenoma. Issue 1 (January 2015) - Petersson, Fredrik
<x xml:space="preserve">Abstract</x> Abstract This paper attempts to summarize the clinico-pathological characteristics of the process and outcome of acquisition of a higher degree of malignancy in various epithelial neoplastic conditions of the salivary glands. This process has variably been referred to as "dedifferentiation", "tumor progression" and "high-grade transformation", of which the latter is the preferred designation. The biological properties of an increased degree of malignancy in salivary gland tumors (increased capacity for invasion and destructive growth, increased propensity for metastatic spread and thus increased likelihood of killing the host) are generally reflected in classic morphological features of malignancy, including increased cytonuclear pleomorphism, nucleolar prominence, increased number of mitotic figures and the occurrence of atypical forms, increased propensity for and extent of necrosis, increased irregular interface between the tumor and the surrounding host tissue and increased probability of detecting perineural tumor growth.